2003
DOI: 10.1016/j.virol.2003.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Completion of trimeric hairpin formation of influenza virus hemagglutinin promotes fusion pore opening and enlargement

Abstract: For influenza virus hemagglutinin, an N-cap structure, created at low pH, interacts with membrane-proximal residues (173-178), bringing fusion peptides and membrane-spanning domains close together. Mutational analysis was used to define the role of these interactions in membrane fusion. For all N-cap mutants, both lipid and aqueous dye spread was greatly reduced. Mutation at residues that interact with the N-cap did not reduce levels of fusion, except for substitutions made at residue I173. For N-cap and I173 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 48 publications
1
45
0
Order By: Relevance
“…Note that many of the curvature-generating proteins involved in membrane remodeling lack transmembrane domains (66). The finding that HA2* does not produce fusion pores large enough to allow passage of 10-kDa fluorescent dextran (Stokes radius of 2.4 nm) and does not produce syncytia substantiates the hypothesis that the transmembrane domain (and perhaps its interactions with the fusion peptide) as well as the cytoplasmic domain of HA can be especially important for later fusion stages including fusion pore expansion (26,57,67,68).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Note that many of the curvature-generating proteins involved in membrane remodeling lack transmembrane domains (66). The finding that HA2* does not produce fusion pores large enough to allow passage of 10-kDa fluorescent dextran (Stokes radius of 2.4 nm) and does not produce syncytia substantiates the hypothesis that the transmembrane domain (and perhaps its interactions with the fusion peptide) as well as the cytoplasmic domain of HA can be especially important for later fusion stages including fusion pore expansion (26,57,67,68).…”
Section: Discussionmentioning
confidence: 75%
“…4, A and B, and 5A). A single amino acid substitution at position 173 (I173E), detrimental for HA-mediated fusion (26), significantly inhibited the fusogenic activity of HA2*. Similarly, a substitution of glutamic acid for the glycine in the N terminus (G1E) of HA2 that is known to inhibit HA-mediated fusion (22) resulted in an almost complete loss of the fusogenic activity of the HA2*.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was subsequently shown that for HIV Env, the formation of those 6HBs that participate in fusion occurs late in the process, and bundle formation is completed only after a pore has formed (28). In contrast to HIV Env, 6HBs may form prior to pore formation for Env of avian sarcoma and leukosis virus (27) and for HA of influenza virus (5,39). For HIV Env, the sequence of amino acids intervening between the fusion peptide and HR2 is relatively short, whereas for avian sarcoma and leukosis virus Env and influenza HA, it is much longer.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, HRB binds into the grooves between adjacent HRA monomers in an antiparallel orientation, forming a hairpin structure that brings the FP and TM domains into juxtaposition (12, 64). Peptides derived from the HR regions inhibit viral entry by binding specifically to their complementary regions in the vFGP (8, 54, 58), thereby preventing formation of the hairpin structure which couples protein refolding directly to membrane fusion (5,38,42,57). While most class I vFGPs have short linker regions between their HR regions, the paramyxovirus F protein has a two-domain insertion of approximately 250 residues (10) which may serve as a molecular scaffold to help control the release and refolding of the FP and HR regions.…”
mentioning
confidence: 99%